Global rivalries from the cold war to Iraq (Vistaar, 2006)
"Offering a highly original analysis of world events, especially in the light of the Iraq war, Kees van der Pijl explores the history and development of relations between major countries in the international community. He examines the impact that successive wars and changes in the global political economy have had on the way states relate to each other today." "The author argues that the rise of the English-speaking West has created rivalries between contender states that are never entirely put to rest. With each round of Western expansion, new rivalries are created. Offering a truly global analysis that covers every area of the world - from Europe and America to China, the Middle East, Latin America and Russia - he explores the development of international relations post-WWII, and questions whether the neoliberal project and its human rights ideology have collapsed back into authoritarianism under the guise of the 'war on terror'. Book jacket."--Jacket.